PELAKSANAAN PERJANJIAN ASURANSI KENDARAAN BERMOTOR DENGAN KLAUSULA ALL RISK ANTARA PIHAK NASABAH DAN PIHAK PENANGGUNG KAJIAN MENURUT UNDANG-UNDANG NOMOR 40 TAHUN 2014 TENTANG PERASURANSIAN DI PT ASURANSI WAHANA TATA PERWAKILAN KUPANG - Ibrahim Setiawan Hamid; Darius Mauritsius; Chatryen Megawati Dju Bire (STKIP Subang, 2026)
This study analyzes the implementation of motor vehicle insurance agreements with the All Risk clause between policyholders and insurers at PT Asuransi Wahana Tata Kupang Representative based on Law Number 40 of 2014 concerning Insurance. The research aims to examine how the insurance agreement is implemented in practice and identify the obstacles that arise in its execution. This study uses an empirical legal research method with a qualitative descriptive approach. Data were collected through interviews, observation, and literature study. The results show that the implementation of All Risk motor vehicle insurance agreements has generally been carried out in accordance with applicable legal provisions and the principles of insurance law, including indemnity and utmost good faith principles. However, several obstacles were found, such as low public understanding of policy contents, lack of transparency in information delivery, administrative constraints in the claim process, and legal issues related to standard clauses. These factors often lead to misunderstandings between insurers and policyholders, which may result in disputes. Therefore, improvements in transparency, legal education, and balanced protection between parties are necessary to ensure the effectiveness of insurance implementation.